"Brave and Prudent Soldiers": The Virtue of Courage in The Sadness of Christ. (June 2016) - Lyter, Veronica
Abstract : This paper explores Thomas More's concept of courage as it is expressed in the hand-written notes in his personal Psalter, and in the example of Christ and His "brave and prudent soldiers" in The Sadness of Christ . These texts elaborate a view of courage that builds upon and expands the classical conception of virtue by appropriating it in a Christian context. According to More and the classical philosophers, courage requires an element of prudence and does not preclude feelings of fear. But for More, Christian prudence is predicated upon knowledge of man's supernatural end and the need for grace. The example of Christ provides a model of Christian courage for souls who experience fear. His agony in the garden shows that fear does not inhibit courage but can strengthen it by fostering humility, an element that is not found in the classical notion of virtue. The humble self-knowledge that arises from the experience of fear leads one to turn to God in prayer for strength and consolation, which allows for the ultimate conquering of fear.